Exploring hematological diversity, a comprehensive study of CBC variations among the population of Tehsil Kot-Momin Sargodha - Kamran Arzoo; Muhammad Aslam Shaikh; ZafarLatif Awan; Mudaser Hussain Abbasi; Awais Anwar; Amna Akram (Journal of University Medical & Dental College, 2024)
Objectives: To ascertain the diversity and patterns observed in the complete blood count within the population of Tehsil Kot-Momin , Sargodha.Study Design: Observational Cross Sectional StudyPlace of Study: Rai Medical College,SargodhaMaterials & Methods: A comprehensive collection of 401 CBC samples was meticoulously acquired from individuals at Medina Medical Complex in Kot-Momin ,Sargodha, subsequent to securing verbal informed consent. Subsequent research activities were conducted at Rai Medical College,Sargodha, post-recipt of sanction from the institutional ethical review committee. The time frame for data accumulation extended from june 2023 through August 2023 and the results were analyzed on SPSS Ver 27.Results: The study aimed to explore gender differences in hematological parameters among a sample of 401 individuals. Key findings indicated significant gender-based variations in hemoglobin (p < 0.001), total RBC count ( p< 0.001), hematocrit (p <0.001) , platlelt count (p=0.008), and mean platelet volume (MPV) (p=0.033). In this investigation, male subjects were observed to possess higher mean concentration of hemoplobin , total erythrocyte count and hematocrit levels relative to their female counterparts, who demonstrated an augmented mean thrombocyte count. Significantly, the mean thrombocyte volume (MTV)-a proxy for platelet volume - was markedly distinct between genders, alluding to potential differences in thrombocyte function or production. Conversly, the study revealed no statistically significant disparities in parameters such as leukocyte count (WBC) , mean corpuscular volume ( MCV), mean corpuscular hemoglobin (MCH) , mean corpuscular hemoglobin concentration (MCHC), and proportions of hematocrit  (PCT), as well as neutrophil,lymphocyte ,monocyte, eosinophil and basophil counts, thereby indicating a homogeneity in these hematological indices across genders. Conclusion: This study offers a comprehensive analysis of variations in hematological parameters across different groups, highlighting significant differences in hemoglobin , total RBC count, hematocrit, platelet count and mean platelet volume. These findings underscore the potential influence of biological and physiological factors on blood profiles, suggesting a need for personalized approaches in the interpretation of hematological data for clinical or diagnostic purposes.